Improvement of electrospark deposition technology of steel units for drilling rigs and mining equipment - D. N. Korotaev; E. V. Ivanova (Известия высших учебных заведений: Геология и разведка, 2022)
Introduction. The development of modern equipment and technologies for geological exploration and mining processes raises the problem of ensuring the reliability and durability of mechanic units operating under the conditions of elevated temperatures and pressures in the presence of aggressive external environments. In this regard, there is a need to create functional coatings with unique physical, mechanical and operational properties.Aim. To improve the performance of electrospark coatings based on an analysis of a cause-andeffect diagram and a regression study of the technological modes of processing steel units of geological exploration equipment (on the example of hydraulic cylinder rods of drilling pumps).Materials and methods. To harden the steel surfaces of hydraulic equipment parts, the technology of electrospark deposition (ESD) was used on an IMES-1001 mechanized installation using carbide electrodes and various gas media. In order to identify causal relationships between the factors affecting the hardened surface and to establish the most important factors affecting the quality of the formed coating, the Ishikawa diagram method was used and a regression analysis was performed. The adhesion activity of the obtained coatings was assessed by atomic force microscopy on a Solver PRO scanning probe microscope in a semi-contact air scanning mode using NSG10probe sensors with a resonance frequency of 219 kHz and a radius of curvature of the probe tip of 10 nm. When determining the strength of the adhesive interaction of the probe and the surface at one point, the absolute error was 15 nN. Tribological tests were carried out on a 2070-СМТ-1 standard friction machine according to the “disk-shoe” scheme.Results. The obtained cause-and-effect diagram showed that the technological modes of an electrospark deposition installation comprise a determining factor affecting the quality of the formed layers and coatings. In order to identify those process parameters that had the greatest effect, a regression analysis was carried out. The capacitance of the unit capacitors was found to have the greatest impact on the adhesion force formed by the ESD coating. Therefore, in order to reduce the strength of the adhesive interaction of surfaces and, as a result, increase their wear resistance, it is necessary to increase the capacitance of capacitors while reducing the voltage and processing time when implementing the ESD technology. On the basis of tribological tests, it is concluded that the minimum wear rate of coatings can be obtained by alloying the steel surface in an oxygen environment with a carbide electrode based on tungsten carbide with additives of elements that form unlimited solid solutions with the surface material and perform the role of fluxes (Ni-Cr-B-Si).Conclusion. Due to strict requirements to the performance of metal surfaces of units that enter into frictional interaction during the implementation of mining and exploration processes, there is a need to improve existing technologies for creating functional (wear-resistant) coatings.